An extended reverse Hardy–Hilbert’s inequality in the whole plane - Qiang Chen; Bicheng Yang (Journal of Inequalities and Applications, 2018)
Abstract Using weight coefficients, a complex integral formula, and Hermite–Hadamard’s inequality, we give an extended reverse Hardy–Hilbert’s inequality in the whole plane with multiparameters and a best possible constant factor. Equivalent forms and a few particular cases are considered.